Speckle‐tracking analysis based on 2D echocardiography does not reliably measure left ventricular torsion. (3rd October 2012) - Parisi, Valentina; Losi, Maria Angela; Contaldi, Carla; Chiacchio, Elena; Pastore, Fabio; Scatteia, Alessandra; Giamundo, Alessandra; Nardo, Carlo di; Lombardi, Raffaella; Betocchi, Sandro
Summary: Purpose: Worldwide left ventricular (LV) twist is measured by 2D speckle tracking acquiring apical short axis at a LV level where papillary muscles are no longer visible; however, we hypothesized that this methodological recommendation is not enough accurate to obtain a reliable measurement of apical rotation. Methods: We measured twist and untwist rate in 30 healthy subjects by following the earlier method. By 3D echocardiography, we identified two LV apex levels: (i) 3D Apex, defined as the last apical slice at which LV cavity was visible; (ii) 2D Apex, defined as the level where diameters are equal to those of apical LV short axis used for twist analysis in the same subject. The ratio between the distance of 2D Apex and 3D Apex from LV base was calculated and expressed as percentage (2D Apex/3D Apex). Results: 2D Apex/3D Apex was strongly related to the magnitude of twist and untwisting rate ( r = 0·82, P <0·001; r = −0·46, P = 0·015, respectively). The only determinant of twist was 2D Apex/3D Apex ( r 2 = 0·68; r = 0·82; F ratio: 52·6, P <0·001); whereas untwisting rate was influenced by 2D Apex/3D Apex and age ( r 2 = 0·42; r = 0·65; F ratio: 7·7; P = 0·003 for 2D Apex/3D Apex; and P = 0·011 for age). Conclusions: Left ventricular apical level acquisition, even when recorded in a standard manner, determines variability of twist mechanics measurements. Thus, current anatomical markers used to identify LV apex for twist analysis are not reliable and need different standardization. 3D echocardiography may help in such standardization.